Detonation Control for Propulsion Pulse Detonation and Rotating Detonation Engines (Shock Wave and High Pressure Phenomena,, 2018)
This book focuses on the latest developments in detonation engines for aerospace propulsion, with a focus on the rotating detonation engine (RDE). State-of-the-art research contributions are collected from international leading researchers devoted to the pursuit of controllable detonations for practical detonation propulsion. A system-level design of novel detonation engines, performance analysis, and advanced experimental and numerical methods are covered. In addition, the world's first successful sled demonstration of a rocket rotating detonation engine system and innovations in the development of a kilohertz pulse detonation engine (PDE) system are reported. Readers will obtain, in a straightforward manner, an understanding of the RDE & PDE design, operation and testing approaches, and further specific integration schemes for diverse applications such as rockets for space propulsion and turbojet/ramjet engines for air-breathing propulsion. Detonation Control for Propulsion: Pulse Detonation and Rotating Detonation Engines provides, with its comprehensive coverage from fundamental detonation science to practical research engineering techniques, a wealth of information for scientists in the field of combustion and propulsion. The volume can also serve as a reference text for faculty and graduate students and interested in shock waves, combustion and propulsion.